DC priming by M. vaccae inhibits Th2 responses in contrast to specific TLR2 priming and is associated with selective activation of the CREB pathway. - Nina Le Bert; Benjamin M Chain; Graham Rook; Mahdad Noursadeghi (PLoS ONE)
The environmental mycobacterium, M. vaccae has been used in mouse models to support the contemporary hygiene hypothesis that non-pathogenic microorganisms reduce allergy associated T helper (Th)2 responses and inflammatory diseases by augmenting regulatory T cells. However, data for human models and possible mechanisms are limited. We tested the effect of innate immune interactions between human DC and M. vaccae on DC-dependent T cell responses. M. vaccae activation of DC via Toll like receptor (TLR)2 was compared to a specific TLR2 ligand (Pam(3)CSK4) and alternative stimulation with a TLR4 ligand (LPS). M. vaccae induced DC dependent inhibition of Th2 responses, in contrast to Pam(3)CSK4, which had the opposite effect and LPS, which had no polarizing effect. DC maturation, gene expression and cytokine production, in response to each stimulus did not correlate with the specific functional effects. Comparable DC transcriptional responses to M. vaccae and Pam(3)CSK4 suggested that TLR2 mediated transcriptional regulation was not sufficient for inhibition of Th2 responses. Transcription factor enrichment analysis and assessment of signaling events, implicated a role for selective early activation of the CREB pathway by M. vaccae. Further study of the CREB pathway may provide novel insight into the molecular mechanisms of DC-dependent T cell polarization.